Kebumen Cares through Free Circumcision at Taman Winangun Kebumen Islamic Boarding School - Sawiji, Sawiji; Nugroho, Irmawan Andri; Santoso, Dadi (Journal of Community Services and Engagement: Voice of Community (VOC), 2023)
Circumcision is an obligation for Muslims. declared an obligation because it has been exemplified in the sunnah of the Prophet. It is stated in Siroh Nabawiyah that Rasulullah SAW performed circumcision when he was 7 days old. However, socialisation of the sunnah of Rasulullah Muhammad SAW in Indonesian society is mostly carried out when children are 5 years old or older. Currently, circumcision, or what is more commonly referred to ascircumcision," can be done in various ways. The choice of a variety of ways and the effects that arise are also very influential on the costs incurred. The obstacle in general is that the cost of circumcision under the care of a doctor is not affordable for the poor, who are being squeezed by economic problems. Based on this, we intend to organise a mass circumcision social service for poor children. As a medical tertiary institution engaged in the world of medical surgical nursing, the Community Service Team for the Undergraduate Nursing Study Program, Muhammadiyah University of Gombong, is motivated to participate in creating a healthy young generation. This small step is very important for us, especially if the circumcision process brings social values towards a better social life. This mass circumcision programme was carried out at the Tathmainnul Qulub Islamic Boarding School, Taman Winangun, Kebumen, and was attended by 22 participants. With the mass circumcision program, we are sure that we can fully obtain these positive values. Therefore, we are ready and able to be part of this noble step and invite benefactors to participate in it.